Pengaruh Empowerment Terhadap Pengambilan Keputusan Perawat: Kajian Literature Review - Pashar, Imran; Dwiantoro, Luky (Universitas Muhammadiyah Magelang, 2020)
The ability to make ethical problem decisions is a requirement for nurses to carry out the professional nursing practice. Decision making is a systematic approach to resolve a problem. World Health Institution in 2017 identified 98.000 patients died every year because of bad decision making. One strategy in the transformation of organizations in health services today is empowerment. Empowerment is a leadership design that can influence a nurse in decision making. The study aims to know the influence of empowerment leadership on the nurse’s decision making. The method in this paper is a literature review. Search for research articles using a database of sciences from Google Scholar, Science Directs, Clinical Key and the final results found 10 articles to be reviewed. Results: 5 empowerment resources can be used by nurses in improving decision making. The empowerment that contains reward, coercive, expert, referent, and legitimate can be used by nurses in improving decision making Result: 5 sources of empowerment can be used by nurses in improving decision making. The empowerment that contains reward, coercive, expert, referent, and legitimate can be used by nurses in improving decision making. Empowerment leadership style can be an alternative way to improve the quality of nurse decision making. Reward and coercive can influence experience, an expert can influence facts and rational, a referent can affect intuition, and legitimate can affect authority.